Residuum Muscle Activation During Gait in Individuals with Traditional and Osteomyoplastic Amputation. Issue 4 (October 2018) - Kotamraju, Bhanu Prasad; Commuri, Sesh; Mai, A.; Dionne, Carol P.; Day, Jonathan; Ertl, William J.J.
ABSTRACT: Introduction: In this case series, distal residuum muscle activation during self-paced, fast-paced, and load-carrying walking gaits was compared by traditional transtibial amputation (TTA) or transtibial osteomyoplastic amputation (TOA) approach. Method: The activities of the residual muscles (tibialis anterior [TA] and gastrocnemius [GA]) were recorded during the three types of gait that are typically encountered during work-related activities. Results: The study shows that there was substantial muscle activity in both the TA and the GA muscles of a TOA subject. On the other hand, the TA in TTA subjects did not show any appreciable activity during any of the gaits. Although the GA muscle in the intact lower limb was active in the late stance phase in both TOA and TTA subjects, this muscle was also active in the loading phase and in the early swing phase in both the groups. This GA activation occurs consistently with supporting the body weight during early stance and preparing the limb for the swing phase during the gait cycle. Conclusions: The results of this study lay the foundation for future studies that investigate the effect of muscle activity on the health of the residual transtibial limb.